Modeling and simulation of human cardiovascular system - Theint Theint Aye. (2008)
This report deals with modeling and simulation of human cardiovascular system. The purpose of modeling is to obtain the basic equations of current conservations commonly used to describe electrical propagation in the cardiac cells. The cardiac cells are excitable. The excitation of the cardiac cell membrane can be transmitted from one cell to another. The extracellular and intracellular flow determines the electrical currents, which plays on the excitation and transmits through space. For modeling purpose, the myocardium is usually considered as a continuous medium.